An Analysis of Students’ Speaking Skills Through Storytelling at Phase F2 Level - Rieza Nina Yetti; Feby Meuthia Yusuf; Lailatul Husna (JURNAL ARMADA PENDIDIKAN, 2025)
This study aims to analyze students’ speaking ability through storytelling in the F2 phase at SMA Negeri 5 Padang. The study was motivated by observations that many students still face challenges in speaking English fluently and confidently. A descriptive research design was employed, involving 28 students selected through random sampling. Data were collected using a speaking test focusing on pronunciation, grammar, vocabulary, fluency, and comprehension. The results indicate that students’ speaking ability falls into the moderate category with an average score of 63. Pronunciation, grammar, vocabulary, and fluency were categorized as moderate, while comprehension was categorized as high. The main problems identified were nervousness, lack of self-confidence, and limited vocabulary, which affected students’ fluency and performance. This study concludes that storytelling can be an effective medium for improving students’ speaking ability and confidence in English communication.